2016
DOI: 10.1038/srep32986
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive Ability Predicts Survival on a London Trading Floor

Abstract: Interoception is the sensing of physiological signals originating inside the body, such as hunger, pain and heart rate. People with greater sensitivity to interoceptive signals, as measured by, for example, tests of heart beat detection, perform better in laboratory studies of risky decision-making. However, there has been little field work to determine if interoceptive sensitivity contributes to success in real-world, high-stakes risk taking. Here, we report on a study in which we quantified heartbeat detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 47 publications
6
70
1
3
Order By: Relevance
“…It was found that, although both tasks yielded reliable accuracy measures, heartbeat counting scores were unrelated to heartbeat detection scores in this sample of university students. This evidence adds to previous findings that heartbeat counting scores are uncorrelated with heartbeat detection scores on two‐alternative forced‐choice tasks (Forkmann et al, ; Kandasamy et al, ; Knoll & Hodapp, ; Phillips et al, ; Schulz et al, ; Weisz et al, ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It was found that, although both tasks yielded reliable accuracy measures, heartbeat counting scores were unrelated to heartbeat detection scores in this sample of university students. This evidence adds to previous findings that heartbeat counting scores are uncorrelated with heartbeat detection scores on two‐alternative forced‐choice tasks (Forkmann et al, ; Kandasamy et al, ; Knoll & Hodapp, ; Phillips et al, ; Schulz et al, ; Weisz et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Thus, cases for the validity of both the HBC and six‐interval HBD measures have been presented by proponents of these methods while questions of their validity have been raised by critics of each of the methods. Some investigators have reported that performance on the HBC task is related to HBD performance on two‐alternative forced‐choice tasks (Hart, McGowan, Minati, & Critchley, ; Knoll & Hodapp, ), but others have found performance on the two tasks to be uncorrelated (Forkmann et al, ; Kandasamy et al, ; Phillips et al, ; Schulz, Lass‐Hennemann, Sutterlin, Schachinger, & Vogele, ; Weisz et al, ), also see Knoll & Hodapp () . In this context, the current experiment was undertaken in order to clarify the extent to which the HBC task (Schandry, ) and the six‐interval HBD task (Brener et al, ) measure the same or different abilities.…”
Section: Introductionmentioning
confidence: 99%
“…A directional one‐tailed parametric correlation revealed a significant relationship between the two variables ( r = .477; p = .019) . To explore this effect further and given the relatively small sample size for correlation analyses, we followed the rationale set out in Kandasamy et al, , p. 3, creating groups with different levels of dance expertise. A median split was performed on the variable years of dance experience (median = 17.5; range: 8–30 years).…”
Section: Resultsmentioning
confidence: 99%
“…First, as interoception is linked to risk-taking and advantageous decision-making (Werner et al, 2009; Kandasamy et al, 2016), we predicted that individual differences in interoceptive sensibility would predict risk-taking. Second, extending earlier observations (Tice et al, 2001), we predicted that negative emotional states compromise self-control, and thus increase behavioral impulsivity.…”
Section: Introductionmentioning
confidence: 99%